DEVELOPING A SCHOOL-BASED FRAMEWORK FOR DIGITAL CITIZENSHIP IMPLEMENTATION IN CIVIC EDUCATION: INSIGHTS FROM TEACHERS AND EXPERTS IN BANDA ACEH - Ridayani, Ridayani; Utami, Anta Rini; Fajri, Iwan; Bariah, Chairul; Sautunnida, Lia (Pena Cendekia Insani, 2025)
In the digital era, Civic Education must evolve to address students’ online behaviors, responsibilities, and participation as digital citizens. However, many high school educators in Indonesia lack the guidance, confidence, and institutional support to meaningfully integrate digital citizenship into their teaching. This study aims to explore the challenges and needs experienced by Civic Education teachers and experts, and to develop a practical school-based framework for implementing digital citizenship in senior high schools in Banda Aceh. Employing a qualitative research design, data were collected through in-depth interviews with seven Civic Education teachers and three national education experts. Thematic analysis was used to identify key patterns across participant narratives. The findings reveal major challenges, including uncertainty in curriculum integration, low teacher digital literacy, and limited stakeholder collaboration. Teachers expressed a need for structured training, contextualized teaching templates, and stronger institutional support. Based on these insights, the study proposes a three-phase implementation framework: (1) planning and stakeholder engagement, (2) curriculum-based integration using active learning, and (3) continuous evaluation and reflection. The study concludes that successful integration of digital citizenship requires systemic collaboration, professional development, and adaptive policy reforms. These findings contribute theoretically by advancing context-sensitive models of digital civic education grounded in empirical teacher perspectives, and practically by offering an actionable framework to guide schools, policymakers, and curriculum developers in fostering responsible and participatory digital citizens within the Indonesian education system.